Soluble TRAIL is present at high concentrations in seminal plasma and promotes spermatozoa survival. - Zauli, Giorgio; Celeghini, Claudio; Monasta, Lorenzo; Martinelli, Monica; Luppi, Stefania; Gonelli, Arianna; Grill, Vittorio; Ricci, Giuseppe; Secchiero, Paola (Reproduction, 2014)
The expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL(TNFSF10)) and of its receptors (TRAILR1, TRAILR2, TRAILR3, and TRAILR4) have been documented in testis, but the presence of soluble TRAIL in seminal fluid, as well as the potential physiopathological role of the TRAIL/TRAILR system in spermatozoa, has not been previously investigated. Male donors (n=123) among couples presenting for infertility evaluation were consecutively enrolled in this study. The presence of soluble TRAIL was analyzed in seminal samples by ELISA, while the surface expression of TRAIL receptors was investigated by flow cytometry. High levels of soluble TRAIL were detected in seminal plasma (median, 11 621 pg/ml and mean±s.d., 13 371±8367 pg/ml) and flow cytometric analysis revealed a variable expression of TRAIL receptors in the sperm cellular fraction among different subjects. In addition, the effect of physiologically relevant concentrations of recombinant TRAIL was investigated on survival and motility of spermatozoa. Of interest, the in vitro exposure of capacitated spermatozoa to recombinant TRAIL (10 ng/ml) significantly preserved their overall survival. Therefore, the present study demonstrates for the first time the presence of elevated levels of the anti-inflammatory cytokine TRAIL in seminal fluids. Moreover, the demonstration that recombinant TRAIL promotes spermatozoa survival after capacitation suggests potential therapeutic implications.
Keywords: Adult; Apoptosis; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; Humans; Infertility, Male; Male; Receptors, TNF-Related Apoptosis-Inducing Ligand; Semen; Sperm Capacitation; Sperm Motility; Spermatozoa; TNF-Related Apoptosis-Inducing Ligand